THE ROLE OF INTERACTIVE TEACHING METHODS IN DEVELOPING UNIVERSITY STUDENTS’ COMMUNICATIVE COMPETENCE - Gulmira Rakhmonova (TADQIQOTLAR, 2026)
Abstract The development of communicative competence has become one of the primary objectives of modern higher education. In the context of globalization and increasing academic and professional mobility, university graduates are expected to possess not only subject-specific knowledge but also effective communication skills. This study examines the role of interactive teaching methods in developing university students' communicative  competence.  The  research  explores  the  theoretical  foundations  of communicative competence and analyzes the effectiveness of interactive methods such as  role  plays,  discussions,  debates,  case  studies,  project-based  learning,  and collaborative  tasks.  The  findings  suggest  that  interactive  teaching  methods significantly  enhance  students'  linguistic,  sociolinguistic,  discourse,  and  strategic competences by creating authentic communication opportunities and increasing learner engagement.